The legend of the large MCAS gains of 2000-2001. - Gregory Camilli; Sadako Vargas (Arizona State University, 2006)
Issues related to student, teacher, and school accountability have been at the forefront of current educational policy initiatives. Recently, the state of Massachusetts has become a focal point in debate regarding the efficacy of high-stakes accountability models based on an ostensibly large gain at 10th grade. This paper uses an IRT method for evaluating the validity of 10th grade performance gains from 2000 to 2001 on the Massachusetts Comprehensive Assessment System (MCAS) tests in English Language Arts (ELA) and mathematics. We conclude that a moderate gain was obtained in ELA and a small gain in mathematics.